PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR 2020-2023 - Lutvia Wahyu Utami; Ida Subaida; Ardhya Yudistira Adi Nanggala (Fakultas Ekonomi dan Bisnis, 2025)
The food and beverage sector listed on the Indonesia Stock Exchange is one of the fastest growing industries and makes a significant contribution to the national economy. This study aims to determine the effect of Profitability, Sales Growth, and Company Size on Company Value, both directly and indirectly through Capital Structure as an intervening variable. The study focuses on food and beverage companies listed on the IDX in 2020 - 2023. The method used is a quantitative method with a descriptive approach, using purposive sampling to select 9 companies as research samples. Data sourced from annual financial reports available on the official IDX website. Data analysis using Structural Equation Modeling (SEM) with Smart PLS software. The results of the Profitability analysis have a negative and significant effect on Capital Structure; Sales growth has a negative but insignificant effect on Capital Structure; Company size has a negative but insignificant effect on Capital Structure; Profitability has a negative but insignificant effect on Company Value; Sales growth has a positive but significant effect on Company Value; Company size has a negative and significant effect on Company Value; Capital structure has a positive and significant effect on Company Value; Profitability has a negative but insignificant effect on Company Value through Capital Structure; Sales growth has a negative but insignificant effect on Company Value through Capital Structure; Company size has a negative but insignificant effect on Company Value through Capital Structure.